PERSPEKTIF ISLAM DAN PERAWAT MENGENAI SAFE AND HYGIENE TERHADAP PENGGUNAAN MENSTRUAL CUP PADA WANITA - Inka Riana, Anjaeni; Maharani, Fita; Mayastika, Intan; Khansa Nabilah, Rafa; Meirizka, Raisha; Supriyadi, Tedi; Faozi, Akhmad (International Journal Mathla’ul Anwar of Halal Issues, 2025)
The use of menstrual cups is increasingly gaining attention as a hygienic, eco-friendly, and cost-effective alternative to conventional sanitary pads. However, acceptance among Muslim women remains relatively low due to limited health education and concerns regarding religious compatibility. This qualitative study aims to explore the perspectives of healthcare providers and Islamic scholars on the safety and hygiene aspects of menstrual cup use among women. The study involved in-depth interviews with three primary participant groups: menstrual cup users, nurses, and Islamic scholars in the Cimalaka Subdistrict. The findings indicate that, from a medical perspective, menstrual cups are considered safe and hygienic when used properly and accompanied by adequate education. From a religious perspective, scholars stated that menstrual cup use is permissible as long as it does not block the flow of menstrual blood and does not cause harm. The results also reveal that public knowledge about menstrual cups remains low, especially in areas with limited access to information. Religious views play a significant role in influencing women's decisions regarding the use of this product. This study concludes that collaborative education involving healthcare providers, religious leaders, and users is essential to enhance public understanding and acceptance. With the right approach, menstrual cups have the potential to become a widely accepted menstrual management tool that aligns with both health standards and religious values.